Effects of Educational Intervention on Dental Plaque Index in 9-Year-Old Children - Zarabadipour, Mahdieh; Makhlooghi Sari, Mehrnaz; Moghadam, Alireza; Kazemi, Benyamin; Mirzadeh, Monirsadat (International journal of dentistry, 2022)
Background and Aim. Oral hygiene is a quintessential part of our health. Effective oral hygiene training should be commenced from early childhood, and if completed, yields positive results in children. The aim of this study was to evaluate the effects of oral hygiene training on dental plaque index in 9-year-old children of Qazvin city, Iran. Methods. 119 students of third-grade elementary (65 girls and 54 boys) from government and private schools of Qazvin city participated. The dental plaque index of every participant was primarily recorded by Silness and Loe method. Students were trained by a dental student by face-to-face method, and after 2 weeks, dental plaque indices were recorded again for every individual. After index recording and coding, data analysis was done using SPSS version 21. Results. Results showed that the dental plaque index was statistically significantly different before and after training (p<0.001). Conclusion. Based on the results of this study, students’ motivation in addition to proper training, can have a significant impact on oral and dental health. Furthermore, this study shows that face-to-face training along with involving the individual in training and learning was seen as quite helpful.